Overexpression of Laminin 5γ2 Chain Correlates with Tumor Cell Proliferation, Invasion, and Poor Prognosis in Laryngeal Squamous Cell Carcinoma. (15th October 2022) - Yin, Chengyi; Ma, Bingliang; Zhang, Xilin; Lan, Longjiang; Ren, Gang; Xu, Jue; Wang, Jianqiu
Abstract : Objective . Laryngeal squamous cell carcinoma (LSCC) is a common malignant tumor. Laminin 5 γ 2 chain (LAMC2) was reported to be associated with tumorigenesis. This study explored the role of LAMC2 on LSCC progression by regulating the integrin β 1/FAK/Src/AKT pathway. Methods . The level of LAMC2 in 46 LSCC patients was detected by qRT-PCR and western blot. Then the relationship between LAMC2 expression and LSCC malignancy as well as prognosis was analyzed, and the effect of LAMC2 expression on LSCC patient survival was also analyzed using the Kaplan–Meier survival curves. Afterwards, the LSCC cells were transfected with LAMC2 overexpression and knockdown vectors, the effect of LAMC2 on LSCC cell viability, proliferation ability, cell cycle, cell migration, and invasion were detected by CCK-8, colony formation, flow cytometry, wound healing, and Transwell assays. The expression of EMT-related biomarkers and integrin β 1/FAK/Src/AKT signaling-related proteins was detected by western blot. Moreover, the effect of LAMC2 on LSCC tumor growth was evaluated by in vivo xenograft experiments and western blot. Results . LAMC2 was expressed at high level in LSCC tissues and associated with poor prognosis. LAMC2 overexpression increased TU177 cell viability, proliferation ability, promoted cell cycle, cell migration, and invasion capacity. The expression of N-cadherin, vimentin, and integrin β 1/FAK/Src/AKT related proteins was increased, while the expression of E-cadherin protein was decreased. When the LAMC2 knockdown in AMC-HN-8 cells had opposite effects. Furthermore, shLAMC2 decreased tumor volume and the expression of LAMC2, Ki-67 and integrin β 1, but increased the expression of E-cadherin in LSCC tumor-bearing mice. Conclusion . The findings suggested that LAMC2 was overexpressed in LSCC and correlated with poor prognosis. LAMC2 knockdown inhibited LSCC progression by regulating the integrin β 1/FAK/Src/AKT signaling pathway. Therefore, LAMC2 could be a target for LSCC therapy.